Lignocaine versus opioids in coronary intervention: assessing antiplatelet activity and ticagrelor levels (LOCAL) study. (14th October 2021) - Fernando, H; Duong, T; Huynh, K; Noonan, J; Shaw, J; Duffy, S; Nehme, Z; Smith, K; Myles, P; Meikle, P; Peter, K; Stub, D
Abstract: Background: Opioid analgesia impairs the bioavailability and antiplatelet effect of oral P2Y12 inhibitors prompting investigation of mitigation strategies including identifying alternative analgesic agents. Purpose: To assess the impact of intravenous fentanyl and lignocaine on the bioavailability and antiplatelet effect of ticagrelor in patients with unstable angina and non-ST elevation myocardial infarction, as well as their procedural analgesic efficacy and safety. Methods: The LOCAL trial was a prospective, single centre, double-blind, randomized, controlled trial where intravenous lignocaine was the experimental analgesic agent assessed in this trial compared to intravenous fentanyl as procedural analgesia during coronary angiography and percutaneous coronary intervention. Patients with an indication for dual antiplatelet therapy and no contraindication were given 180mg of ticagrelor orally as integral tablets with 250 mL of tap water at the end of the case. Blood was sampled at time 0, 0.5, 1, 2 and 4 hours post administration of ticagrelor for pharmacokinetic and comprehensive pharmacodynamic analysis. Results: Seventy patients undergoing coronary angiography with an indication for ticagrelor loading were included in the pharmacokinetic and pharmacodynamic analysis. Plasma ticagrelor levels at 2 h post loading dose were significantly lower in the fentanyl compared to lignocaine treatment arm (476 vs. 792 ng/mL, p=0.02, see figure 1). The area under the plasma-time curves for ticagrelor (987 vs. 2189 ng.h/mL, p=0.001) and its active metabolite (173 vs. 394 ng.h/mL, p<0.001) were both significantly lower in the fentanyl arm. Platelet reactivity assessed by the VerifyNow assay was higher at all time points after baseline in the fentanyl compared to lignocaine arm. The VASP flow cytometry assay demonstrated higher platelet reactivity at 2 hours in the fentanyl group (40% vs. 22% platelet reactivity index, p=0.001). The Multiplate Analyzer demonstrated higher platelet reactivity in the fentanyl arm at 60 minutes (43 vs. 26 area under the curve units, p=0.001) as did expression of activated platelet GpIIb/IIIa receptor (2829 vs. 1426 geometric mean fluorescence intensity (GMFI), p=0.006) and P-selectin (439 vs. 211 GMFI, p=0.001). High on-treatment platelet reactivity (HPR) was significantly higher in the fentanyl arm at 60 min using the MPA (41% vs. 9%, p=0.002) and 120 min using the VFN (30% vs. 3%, p=0.003) and VASP (37% vs. 6%, p=0.002) assays (see figure 2). Both drugs were well tolerated with a high level of patient satisfaction (fentanyl 94% vs. lignocaine 97%, p=0.56). Conclusion(s): Unlike fentanyl, lignocaine does not impair the bioavailability or delay the antiplatelet effect of ticagrelor. Both drugs were well tolerated and effective with a high level of patient satisfaction for procedural analgesia. Systemic pain medication during PCI should be reconsidered and if performed, lignocaine is a beneficial alternative to fentanyl. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): TBA